Relationship between Snacking Patterns, Diet Quality and Risk of Overweight and Abdominal Obesity in Children - Nicklas, Theresa A.; O’Neil, Carol E.; Fulgoni, Victor L. (International Journal of Child Health and Nutrition, 2013)
<!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Snacking is very common among Americans; the impact of variety of snacking patterns on nutrient intake and weight status is unclear. This study examined the associations of snacking patterns on nutrient intake and weight in U.S. children 2-18 years (n=14,220) participating in the 2001-2008 National Health and Nutrition Examination Survey. Cluster analysis generated 12 distinct snacking patterns, explaining 57% of variance in total calories consumed. Only 8% of the children did not consume snacks on the day of the 24-hour recall. Cakes, cookies and pastries was the most common snacking pattern (16%) followed by miscellaneous snacks (e.g. whole milk, orange juice and meat/fish/poultry; 13%), and crackers and salty snacks (10%). Most snacking patterns resulted in higher total energy intake than the no snack pattern. After controlling for energy intake, most snacking patterns resulted in higher intakes of fiber; vitamins A, C, B12, and K; riboflavin; folate; potassium; calcium; zinc; and magnesium than the no snack pattern. However, most of the snacking patterns resulted in higher total intake of saturated fatty acids, solid fats, added sugars, and sodium (nutrients to limit). Several of the snacking patterns (i.e. cakes/cookies/pastries, crackers/salty snacks, sweets, and other grains) were associated with a reduced risk of overweight and abdominal obesity. Overall, several snacking patterns compared with non-snackers had better diet quality and were less likely to be overweight or obese and less likely to have abdominal obesity. Education is needed to improve snacking patterns in terms of nutrients to limit in the diet. <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>